The relationship between the mobbing situation of healthcare workers and their conflict action styles - Eserler, Merve; Sevinç, Nergiz; Nacar, Erkay; Arıcan, Ali Ayberk (Scientific Reports in Medicine, 2025)
Objective: This study aims to examine whether there is a relationship between exposure to mobbing behaviors and conflict action styles among healthcare workers in Karabük Province.Material and Method: This is a descriptive and cross-sectional study conducted with 225 healthcare workers in Karabük between May 15, 2023, and August 15, 2023. The data were collected using the Sociodemographic Information Questionnaire, the Mobbing Scale, and the Conflict Action Styles Scale.Results: The participants’ average score on the mobbing scale was found to be 82.15±44.10. Among the sub-dimensions of the mobbing scale, the highest score was obtained in the “relationships with colleagues” sub-dimension. Participants scored the highest in the “facilitating approach” sub-dimension of the Conflict Action Styles Scale. A significant difference was found between healthcare workers’ exposure to mobbing and their marital status, profession, workplace, weekly working hours, job satisfaction, and smoking status. Additionally, significant differences were found between conflict action styles and gender, education, profession, weekly working hours, and job satisfaction.Conclusion: Healthcare professionals are at risk of experiencing mobbing. This is an important issue that needs attention in terms of employee satisfaction and quality of life. Emphasizing mobbing and conflict action styles in training, implementing more comprehensive legal regulations, and improving working conditions are considered to be beneficial measures.
Keywords: Healtcare workers; Mobbing; Conflict action styles